Introducing a conceptual framework for the strategic classification of state-sponsored social entrepreneurship a conceptual study / Amir Forouharfar, Seyed Aligholi Rowshan and Habibollah Salarzehi - Forouharfar, Amir; Rowshan, Seyed Aligholi; Salarzehi, Habibollah (Penerbit UiTM (UiTM Press), 2019)
Scholars of social entrepreneurship have yet to propose a classification of strategies employed by states to promote SE. The paper's aim is to introduce a conceptual framework for state-sponsored SEs to fill this gap. Such a necessity rises out of the strategic study of the states' role in the promotion of SE intra- and extraterritorially. The paper not only propose strategic mix for the formulation of state-sponsored SE, but also presented a conceptual framework based on the tendency of states toward four orientations of internationalism, internalism, governmentalism and volunteerism for pursuing SE in a macro-scale. Finally, four comprehensive SE strategies namely Opened Door Strategy, Closed Door Strategy, Global Citizen Strategy and Country Citizen Strategy based on the four orientations were proposed. The theoretical implication of the framework is in its contribution to the classification of governmentally promoted SE for a more clarified study and teaching of SEs in the academic context. Its practical implication is in its application as a guideline for sound formulation of SE strategies by public organisations in the public and third sector contexts.